Que faire (with Discourse)? A materialist approach to discourse, ideology and politics in neoliberal conjuncture - Romé, Natalia (2020)
Althusser’s Que Faire? (2018) allows for a critical revision of the “discursive turn” in current social and political theory. As Pêcheux shows, the influences of Spinoza and Freud can be recognized and elaborated on to develop a clinical theory of discourse capable of taking into account overdetermination and class struggle in a rigorous way.